Genomic Profiling Reveals Synchronous Bilateral Lung Adenocarcinomas With Distinct Driver Alterations of EML4-ALK or TPM3-ROS1 Fusion: A Case Report - Tan, Benxu; Jiang, Xuan; Wang, Ruping; Tang, Cuiping; Liu, Sisi; Wu, Xue; Xia, Lei; Yu, Xian; Yang, Zhenzhou (Frontiers in Oncology, 2019)
Background:ALK and ROS1 rearrangement accounts for 3–6% and 1–3% of non-small cell lung cancers, respectively, while coexistence of them in the same patient is extremely rare. Only three cases have ever been reported with concurrent ALK/ROS1 fusions in the same tumor indicating tumor heterogeneity. Therefore, comprehensive genetic profiling via next-generation sequencing (NGS) is needed to provide fully molecular diagnosis. Case Presentation: A 50-year old Chinese female with resectable stage IB bilateral lung adenocarcinomas (ADCs) harbored EML4 exon 6-ALK exon 19 and TPM3 exon 8-ROS1 exon 35 fusions in the right lower and the left upper tumors, respectively, identified by clinical NGS test targeting 425 cancer-relevant genes. The results were further confirmed at RNA level using RNA-seq. Genomic evolution analysis reveals that these bilateral tumors are synchronous multiple primary lung cancers with no shared somatic alterations for both genes and arm-level copy number variations (CNVs). No recurrence was observed during 12 months of post-surgery follow-up. Conclusions: Our case is the first report of concurrent ALK/ROS1 fusions as distinct driver events of synchronous multiple primary lung cancers, and highlights the importance of individual genetic testing for each of the multiple primary tumors for fully molecular diagnosis and precise treatment decision-making.